Eco-Theological Symbolism in Raayatul ‘Izz, a Poem by Sayyid Idrus Al-Jufri: An Ecocritical Analysis Based on Greg Garrard’s Six Dimensions - Eva Annisa Anwar; Minatur Rokhim; Muhammad Ali Raaf Sanjani (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Using an ecocritical approach, this study examines the ecological and spiritual values embedded in Raayatul ‘Izz, a poem by Sayyid Idrus Al-Jufri. Ecocritical studies of Arab-Indonesian religious poetry remain relatively limited, particulary those that explore natural symbolism in the works of Indonesia’s archipelago scholars. This research positions literature as a moral-spiritual medium for fostering ecological awareness amid environmental degradation in Indonesia, such as air, marine, and terrestrial pollution. The study employs a qualitative descrptive method through close reading, coding based on Greg Garrard’s ecocritical dimensions, and eco-theological interpretation. The findings indicate that the poem explicitly presents only the dimensions of “earth” and “wilderness”, manifested through natural imagery such as the sky, the earth, and mountains within its stanza as symbols of fertility, cosmics balance, and submission to the will of God. These representations of nature construct an interconnecion between religious nationalism, ecological consciousness, and spiritual responsibility within the poem’s structure of meaning. The poem thus builds a synthesis of love for the homeland, environmental awareness, and spiritual responsibility, thereby enriching ecocritical discourse in the study of Arab religious literature through the integration of Garrard’s ecocriticism and Islamic eco-theology.